CREB-binding protein plays key roles in juvenile hormone action in the red flour beetle, Tribolium Castaneum - Xu, Jingjing; Roy, Amit; Palli, Subba Reddy (Scientific reports, 2018)
Juvenile hormones (JH) and ecdysteroids regulate many biological and metabolic processes. CREB-binding protein (CBP) is a transcriptional co-regulator with histone acetyltransferase (HAT) activity. Therefore, CBP is involved in activation of many transcription factors that regulate expression of genes associated with postembryonic development in insects. However, the function of CBP in JH action in insects is not well understood. Hence, we studied the role of CBP in JH action in the red flour beetle, Tribolium castaneum and the Tribolium cell line. CBP knockdown caused a decrease in JH induction of genes, Kr-h1, 4EBP and G13402 in T. castaneum larvae, adults and TcA cells whereas, Trichostatin A [TSA, a histone deacetylase (HDAC) inhibitor] induced the expression of these JH-response genes. Western blot analysis with specific antibodies revealed the requirement of CBP for the acetylation of H3K18 and H3K27 in both T. castaneum and TcA cells. Chromatin immunoprecipitation (Chip) assays showed the importance of CBP-mediated acetylation of H3K27 for JH induction of Kr-h1, 4EBP, and G13402 in TcA cells. These data suggest that CBP plays an important role in JH action in the model insect, T.castaneum.
Keywords: genový knockout; Juvenile Hormones; Animals; CREB-Binding Protein; Gene Knockout Techniques; Tribolium; Gene Expression Regulation, Developmental; acetylace; protein vázající CREB; histony; hmyzí proteiny; juvenilní hormony; Acetylation; Insect Proteins; Histones; zvířata; vývojová regulace genové exprese